THE INFLUENCE OF MARKETING MIX ON PURCHASING DECISIONS FOR GROUND MACKEREL AT UMKM EVI TENGGIRI - Sianturi, Lilis Suriani; Yuristia, Rahmi; Cahyadinata, Indra; Rahayu, Heny Sulistyawati Purwaning; Reswita, Reswita (Jurnal Perikanan Unram, 2025)
Bengkulu City has abundant fishery resources, with total fishery yields reaching 32,757 tons. UMKM play an important role in local economic growth, one of which is Evi Tenggiri UMKM, which focuses on ground fish products. Problems in UMKM, such as the unknown influence of marketing to support the success of UMKM. This study aims to analyze the effect of the 4P marketing mix on purchasing decisions for ground mackerel at Evi Tenggiri UMKM. The research location was chosen purposively. Data was obtained from consumers who had bought ground mackerel, with a total sample of 96 respondents determined using the Lemeshow technique. The analysis was carried out descriptively quantitatively with multiple linear regression to measure the effect of the independent variable on the dependent variable. In addition, classical assumption tests such as normality, multicollinearity, heteroscedasticity, and hypothesis testing were carried out to ensure the validity of the model. The F test results obtained that the product, price, place, and promotion variables simultaneously affect purchasing decisions. The t test results for product and price variables show an influence on purchasing decisions. The t test results for the place and promotion variables have no effect on purchasing decisions.